Association of Hepatoma Arterial-embolization Prognostic Score with Survival in Hepatocellular Carcinoma Patients undergoing Transcatheter Arterial Chemoembolization - Ekacitta, Arfika Wida; Kholili, Ulfa; Thamrin, Husin; Boedi Setiawan, Poernomo; Sugihartono, Titong; Maimunah, Ummi; Prasetyo Adi, Garry; Rakateja, Made Bayu A. (Journal of Neonatal Surgery, 2025)
Introduction: Hepatocellular carcinoma (HCC) ranked as the third leading cause of cancer-related deaths worldwide. Hepatoma Arterial-embolization Prognostic (HAP) score was suggested as a survival predictor for HCC patients undergoing Transcatheter Arterial Chemoembolization (TACE). Objectives: This study aimed to analyse the association of HAP score with survival in HCC patients undergoing TACE. Methods: This was survival analysis with longitudinal study. The Kaplan-Meier curve was used for survival analysis, while Cox Regression test was used to analyse univariate and multivariate association between HAP score and its components to survival. Results: There were 100 patients HCC who underwent TACE at a tertiary hospital between January 2019 and September 2022. The overall survival (OS) median was 7 months, while the 12-months survival rate was 9%. The 12-months survival rates of HAP A, HAP B, HAP C and HAP D were 25%, 23.3%, 0 and 0, respectively. There was association between HAP score and 12 months’ survival of HCC patients undergoing TACE (hazard ratio (HR) 3.187, 95% confidence interval (CI) 2.002–5.074, p<0.001). Conclusions: HAP score has a prognostic value in predicting survival outcomes for HCC patients undergoing TACE.